Color stability, surface roughness and microhardness of composites submitted to mouthrinsing action - Marília Salomão Campos Cabrini Festuccia; Lucas da Fonseca Roberti Garcia; Diogo Rodrigues Cruvinel; Fernanda de Carvalho Panzeri Pires- (University of São Paulo, 2012)
OBJECTIVE:The purpose of this study was to evaluate the effect of mouth rinse solutions on color stability, surface roughness and microhardness of two composite resins. MATERIAL AND METHODS: Fifty test specimens of each composite (Filtek Z250 and Z350; 3M ESPE) were made using a teflon matrix (12x2 mm). Color, surface roughness and Knoop microhardness baseline measurements of each specimen were made and specimens (n=10) were immersed in 5 mouth rinse solutions: G1: distilled water (control), G2: Plax Classic, G3: Plax alcohol-free; G4: Periogard, and G5: Listerine. Final measurements of color, roughness and microhardness were performed and the results submitted to statistical analysis (2-way ANOVA, Bonferroni 's test; p<0.05). RESULTS: The most significant color change was observed for Z250 when immersed in Listerine (p<0.05). Z350 showed greater color change when immersed in Plax alcohol-free (p<0.05), but with no significant difference for Listerine (p>0.05). With regard to roughness, both composites showed significant changes when immersed in Listerine in comparison with Plax alcohol-free (p<0.05). Microhardness of Z350 was shown to be significantly changed when the composite was immersed in Plax alcohol-free (p<0.05). CONCLUSION: Composite changes depended on the material itself rather than the mouth rinse solution used.